Inhomogeneous broadening of the conductance histograms for molecular junctions - Bopp, Julian M.; Tewari, Sumit; Sabater, Carlos; Ruitenbeek, Jan M. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We demonstrate that the notched-wire mechanically controllable break junction technique can be exploited for the study of single molecule junctions. We have developed a protocol for deposition of thiol-coupled molecules onto Au electrodes from solution. We find surprisingly sharp conductance historgrams at low temperatures, which suggest that the commonly observed large width of the peaks in conductance historgams is the result of inhomogeneous broadening.